2015
DOI: 10.1177/1352458515607650
|View full text |Cite
|
Sign up to set email alerts
|

Regional cortical thinning in multiple sclerosis and its relation with cognitive impairment: A multicenter study

Abstract: Objectives: The objectives of this paper are to compare in a multicenter setting patterns of regional cortical thickness in patients with relapsing–remitting multiple sclerosis (RRMS) and cognitive impairment (CI) and those cognitively preserved (CP), and explore the relationship between cortical thinning and cognitive performance. Methods: T1-weighted isotropic brain scans were collected at 3T from seven European centers in 60 RRMS patients and 65 healthy controls (HCs). Patients underwent clinical and neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 49 publications
3
37
1
Order By: Relevance
“…In line with previous studies, we found significantly reduced cortical, hippocampal, and deep GM volumes in patients with MS who were CI compared with CP. Reduced neocortical volume 2,3,7,9 and a widespread pattern of regional GM atrophy 15,16,29 have been frequently associated with cognitive impairment in MS, as also shown by a previous investigation of the same patient cohort. 16 GM pathology is known to be substantially present in MS from the earliest stages of the disease and is strongly associated with CI not only in cross-sectional but also in longitudinal studies.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In line with previous studies, we found significantly reduced cortical, hippocampal, and deep GM volumes in patients with MS who were CI compared with CP. Reduced neocortical volume 2,3,7,9 and a widespread pattern of regional GM atrophy 15,16,29 have been frequently associated with cognitive impairment in MS, as also shown by a previous investigation of the same patient cohort. 16 GM pathology is known to be substantially present in MS from the earliest stages of the disease and is strongly associated with CI not only in cross-sectional but also in longitudinal studies.…”
supporting
confidence: 75%
“…The results of regional analysis of GM and WM damage by using surface-based 15 Table). Sex did not differ between HC and patients with MS (P ϭ .7), whereas HC were younger than patients with MS (P ϭ .006).…”
Section: Subjectsmentioning
confidence: 99%
“…Our finding of individual measures of lesion connectivity will have to be further investigated in this context. Particularly for cognitive function, where network disruption 35 and cortical atrophy 14, 22 have been found to be correlated to specific cognitive deficits, the disruptive effect with lesional connectivity and its eventual impact on degenerative measures need further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…17, 18, 21 Cortical segmentations were manually inspected for errors, and re-analysis through the pipeline was performed after lesion filling on the WM segmentation maps, correcting for segmentation errors due to juxtacortical hypo-intensities on T1 images. 22 …”
Section: Methodsmentioning
confidence: 99%
“…The Aβ plaques, neurofibrillary tangles and significant volume atrophy have all been reported in the insula in MCI and AD patients (Karas et al, 2004;Braak et al, 2006;He et al, 2015;Ting et al, 2015;Zhao Z. L. et al, 2015). Furthermore, wholebrain correlational analyses revealed that cognitive performance was associated with the volume (Farrow et al, 2007;Lu et al, 2016;Tillema et al, 2016), functional activity and intrinsic connectivity of the insula in MCI patients (Xie et al, 2012;Nellessen et al, 2015).…”
Section: Discussionmentioning
confidence: 90%